Integrated management of Rhizoctonia solani causing sheath blight of rice (Oryza sativa) - KUMAR, PANKAJ; KUMAR, ANIL; SINGH, RAM (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out at CCSHAU Rice Research Station, Haryana, to manage sheath blight of rice (Oryza sativa L.) caused by Rhizoctonia solani Kuhn through host resistance, botanical extracts, and to develop a spray schedule of best two botanical extracts, i.e. garlic cloves and turmeric powder in combination with the best two fungicides, viz. azoxystrobin 18.2% + difenoconazole 11.4% SC and thifluzamide 23.9% SC. Out of 307 rice genotypes screened during kharif 2016 and 2017, none was found highly resistant against sheath blight. However, only one genotype (RMS-BL-6) showed consistent resistance reaction during both the years while five entries (MR 8333, KNM 1730, PAU 7111-1-1-0, RP 5141-432-10-3-2 and VL 32197) showed a moderately resistant reaction. The rice genotype RMS-BL-6 also showed moderate resistance to bacterial blight, and was moderately susceptible to stem rot. Extracts of garlic cloves and turmeric powder were found effective and reduced the vertical disease spread (relative lesion height) by 36.62% and 35.38% along with 11.59% and 10.85% enhanced grain yield of paddy respectively. Among combination treatments, application of azoxystrobin 18.2% + difenoconazole 11.4% SC at 1 day after inoculation (DAI) followed by extract of garlic cloves at 11 days after inoculation was highly effective and statistically at par with two applications of azoxystrobin 18.2% + difenoconazole 11.4% SC (at 1 and 11 DAI) and thifluzamide 23.9% SC (at 1 and 11 DAI); application of thifluzamide 23.9% SC (1 DAI) followed by azoxystrobin 18.2% + difenoconazole 11.4% SC (11 DAI) and vice-versa.